Atraumatic Restorative Treatment and Dental Anxiety in Outpatients Attending Public Oral Health Clinics in South Africa - Steffen Mickenautsch, BDS; Jo E. Frencken, PhD; Martin A. van’t Hof, PhD (Blackwell Synergy, 2007)
This study was undertaken to test the hypotheses that using the atraumatic restorative treatment (ART) approach results in lower patient anxiety and that lower anxiety leads to higher restoration/extraction ratios.